Business R&D Expenditure in the ICT Sector: Effects on Business Performance Indicators - Ján Huňady; Peter Pisar; Ina Durcekova (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Firms in information and communication (ICT) sector are often considered as an important element of business innovation performance in the economy. This paper is focused on examining their share on innovation and total research and development (R&D) expenditure in selected European countries. Moreover, our goal is to test the potential effect of R&D expenditure on selected business performance indicators. We used panel macro-level data from 24 countries during the years 2008- 2016. Based on the results of panel regression analysis we found empirical evidence for the positive effect of R&D expenditure on value-added and apparent labour productivity in the ICT sector. This fact could be to some extent attributed to the innovation of products and processes. The highest share of business R&D expenditure in ICT is present in Nordic countries such as Island, Norway and Finland. Firms in ICT appear to be more above-average innovative and represent a significant share of total business R&D expenditure.
Keywords: O30; G31; M21; 330; business R&D expenditure; business innovation; ICT sector; business performance; financial indicators